2019
DOI: 10.1097/rct.0000000000000832
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Contrast-Enhanced Spectral Mammography in Comparison to Magnetic Resonance Imaging in Breast Lesions

Abstract: ObjectiveThe aim of this study was to evaluate the diagnostic value between contrast-enhanced spectral mammography (CESM) and breast magnetic resonance imaging (MRI) in breast disease.MethodsTwo hundred thirty-five patients who were suspected of having breast abnormalities by clinical examination or mammography underwent CESM and MRI examination. Using histopathologic results as the criterion standard, the diagnostic performance of CESM and MRI was investigated. The areas under receiver operating characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 16 publications
2
57
0
3
Order By: Relevance
“…In another study done by Xing et al [19], the sensitivity, PPV, and NPV of CEM were comparable to those of MRI. However, the specificity of CEM was higher than that of MRI [19].…”
Section: Discussionmentioning
confidence: 68%
“…In another study done by Xing et al [19], the sensitivity, PPV, and NPV of CEM were comparable to those of MRI. However, the specificity of CEM was higher than that of MRI [19].…”
Section: Discussionmentioning
confidence: 68%
“…A total of 8 studies published between 2003 and 2019 were included in the meta-analysis analysing a total of 945 lesions, of which 36 were DCIS (range 18–263) [ [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] ](see Table 1 ). Total number of included patients were 684 in 7 studies (Tohamey and colleagues did not reported number of included patients and did not reply to our kind request to provide additional data).…”
Section: Resultsmentioning
confidence: 99%
“…Recent advances in digital x-ray system development have also facilitated the design of approaches such as contrast-enhanced spectral mammography (CESM) that can overcome many of the limitations of mammography and achieve diagnostic e cacy comparable to MRI. Xing et al [19] found that CESM achieved higher speci city than MRI (89.5% vs 80.2%) and that the same was true for its positive predictive value (94.7% vs 90.5%). However, this approach is limited by the fact that it is unable to image the entire chest wall and axilla, requires compression, utilizes ionizing radiation, and requires that patients receive iodinated contrast injection.…”
Section: Discussionmentioning
confidence: 93%